Ekoteologi dan Tanggung Jawab Gereja atas Perambaan Hutan di Indonesia - Rusliadi; Yohanes Hasiholan Tampubolon (Te Deum (Jurnal Teologi dan Pengembangan Pelayanan), 2025)
God, as the Creator of the earth and everything in it, declared all creation good, including nature. Through nature, God provides for the survival of all living beings. This paper focuses on forests as part of God’s good creation, emphasizing their crucial role in sustaining ecological balance and providing food sources. However, Indonesia’s forests are in crisis due to rampant encroachment driven by various factors. As stewards of creation, believers—and especially the church—are called to respond. This study urges the church to actively reject forest encroachment and fulfill its cultural mandate as a form of ministry and service. The church must engage in practical steps to protect forests, such as delivering context-relevant environmental sermons, encouraging holistic land stewardship among congregants, offering environmental education, and promoting collective awareness and responsibility. In doing so, the church contributes to preserving God’s creation and demonstrates faithful obedience to the Creator’s mandate.